2016
DOI: 10.18632/oncotarget.11562
|View full text |Cite
|
Sign up to set email alerts
|

An anti-ErbB2 fully human antibody circumvents trastuzumab resistance

Abstract: Trastuzumab, an anti-HER2/ErbB2 humanized antibody, has shown great clinical benefits in ErbB2-positive breast cancer treatment. Despite of its effectiveness, response rate to trastuzumab is limited and resistance is common. Here, we developed a new anti-ErbB2 antibody, denoted as H2-18, which was isolated from a phage display human antibody library. Previous studies have demonstrated that trastuzumab recognizes the juxtamembrane region of domain IV, and pertuzumab, another humanized ErbB2-specific antibody, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 44 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…Extensive studies of mammary cells including breast cancer cells have revealed that 3D cell culture models could more accurately mimic the in vivo signaling, behavior and reaction of cancer cells to drugs than conventional 2D models [ 17 – 20 ]. Here, to further investigate whether the combination of H2-18 and GDC-0941 is synergistic in inhibiting cell proliferation, we treated BT-474, SKBR-3, HCC-1954 and HCC-1419 cells with various concentration ranges of GDC-0941 and H2-18 in 3D culture system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive studies of mammary cells including breast cancer cells have revealed that 3D cell culture models could more accurately mimic the in vivo signaling, behavior and reaction of cancer cells to drugs than conventional 2D models [ 17 – 20 ]. Here, to further investigate whether the combination of H2-18 and GDC-0941 is synergistic in inhibiting cell proliferation, we treated BT-474, SKBR-3, HCC-1954 and HCC-1419 cells with various concentration ranges of GDC-0941 and H2-18 in 3D culture system.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study, we reported an ErbB2 domain I-specific fully human antibody H2-18, which exhibited a great antitumor activity in trastuzumab-resistant breast tumor-bearing nude mice [ 17 ]. However, H2-18 only had a slight inhibition effect on PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 In the same fashion, the human antibody coded H2-18 recognizing an as yet untargeted epitope of the ErbB2 receptor was found to be able to circumvent trastuzumab resistance and to be more effective at inhibiting tumor growth than the combination of trastuzumab and pertuzumab in both in vitro and in vivo pre-clinical models. 43 HuA21 is a chimeric antibody targeted to subdomain I of the ErbB2 extracellular domain and it has been shown to markedly suppress the growth of trastuzumabresistant cells. 44…”
Section: Alternative/improved Trastuzumabmentioning
confidence: 99%
“…Recently the Lu group used the ErbB2 domain I-specific fully human antibody H2-18 to induce programmed cell death in the trastuzumab resistant breast cancer cell line HCC-1954 [136]. Due to the absence of a kinase domain, the ErbB3 receptor has been less appreciated as a potential drug target.…”
Section: Identification and Molecular Characterization Of Erbb Oncmentioning
confidence: 99%